2019
DOI: 10.1159/000503289
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifications as Outcomes of Exercise Interventions Related to Specific Metabolic Alterations: A Systematic Review

Abstract: <b><i>Background:</i></b> Chronic diseases arise as a consequence of an unhealthy lifestyle primarily characterized by physical inactivity and unbalanced diets. Regular physical activity can improve health, and there is consistent evidence that these improvements may be the result of epigenetic modifications. <b><i>Objective:</i></b> To identify epigenetic modifications<b><i></i></b>as outcomes of exercise interventions related to specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 66 publications
0
43
0
4
Order By: Relevance
“…Additionally, acute strenuous exercise (consisting of stepping up and down from a step until complete exhaustion) led to enhanced chronic low-grade inflammation in PBMCs from obese individuals via an imbalance on Histone H4 Acetylation/Histone Deacetylase 2 as compared to lean subjects [65]. Together, these findings suggest that the impact of physical activity in inflammation is dependent of type, intensity, and clinical settings of exercise interventions [54].…”
Section: Physical Activitymentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, acute strenuous exercise (consisting of stepping up and down from a step until complete exhaustion) led to enhanced chronic low-grade inflammation in PBMCs from obese individuals via an imbalance on Histone H4 Acetylation/Histone Deacetylase 2 as compared to lean subjects [65]. Together, these findings suggest that the impact of physical activity in inflammation is dependent of type, intensity, and clinical settings of exercise interventions [54].…”
Section: Physical Activitymentioning
confidence: 91%
“…Studies have shown that some physical exercise may exert anti-inflammatory effects through epigenetic regulation depending on the type of activity, exercise duration, body composition, gender, and age [54]. However, excessive physical activity (i.e.…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, aerobic exercise has been shown to upregulate UPS in healthy mice [ 37 ]. Also, all epigenetic agents are strictly influenced by environmental and lifestyle factors, including physical exercise [ 38 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Evidence exists, not only for the benefit of physical exercise as an epigenetic modulator of brain plasticity and cognition, 7,14 but also for somatic disturbances such as exercise-induced epigenetic modifications in genes related to insulin resistance and type 2 diabetes, inflammation, cardiovascular disease and obesity. 15 The aim of this article is to provide general practitioners (GPs) and primary healthcare workers with an overview of the benefits of physical exercise as an add-on therapy to pharmacological intervention for patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%